Fission Yield Calculation Method and its Effect in Nuclear Fuel Cell Homogenization Calculation - Zaki Su’ud; M. Ali Shafii; Rida SNM (Indonesian Journal of Physics, 2009)
Zero burn-up core capability can eliminate possible super prompt critical accident and make possible of inherent safety feature based on reactivity feedback mechanism. In this concept the maximum excess reactivity is limited below 1 $ of reactivity so that possibility of super prompt accident such as in Chernobyl accident case can be eleminated. This is however need high quality of system analysis, and in this study the effect of fission yield calculation method on the nuclear fuel cell homogenization process is investigated and discussed. This study use SRAC code system to investigate the efect of reactor dependent fission yield distribution calculation. Calculation restults show that this process will has important improvement effect for long life high burnup core.